Alterations in the CTRB2 gene and response to chemotherapy in pancreatic cancer - Khalid Jazieh; Erin E. Carlson; Zafar Siddiqui; Katelyn E. Connelly; Jun Zhong; Jason W. Hoskins; Kari G. Rabe; Ann L. Oberg; Hugues Sicotte; Ryan M. Carr; Laufey T. Amundadottir; Samuel O. Antwi (PLoS ONE, 2026)
Background Pancreatic ductal adenocarcinoma (PDAC) remains a highly fatal malignancy due partly to treatment resistance in many patients. We previously identified a functional germline deletion overlapping exon 6 of CTRB2 (CTRB2ex6) at a PDAC genome-wide risk locus on chr16q23.1. This variant leads to a nonfunctional truncated chymotrypsin protein that accumulates intracellularly and induces endoplasmic reticulum stress. Here, we performed a retrospective study to determine whether CTRB2ex6 deletions are associated with response to chemotherapy, time to cancer progression, or overall survival (OS) in PDAC patients. Methods The study included CTRB2 genotype data from two independent PDAC cohorts (Cohort 1: n = 633; Cohort 2: n = 3,896). We examined associations between CTRB2ex6 deletion status and OS and time-to-progression (TTP) using Cox proportional hazard modeling. TTP was also evaluated in a subset of chemotherapy-treated patients in Cohort 1 (n = 263) to determine the impact of CTRB2ex6 deletion status on chemotherapy response. Results CTRB2ex6 deletions were found in 20% of patients in both cohorts combined (19% in Cohort 1, and 21% in Cohort 2). No significant difference was observed in OS by CTRB2 deletion status in either cohort (Cohort 1: HR = 0.95, p = 0.60; Cohort 2: HR = 1.04, p = 0.43). Among chemotherapy-treated patients in Cohort 1, CTRB2 deletion carriers had a longer median TTP (20.4 vs. 12 months), though this was not statistically significant ( p = 0.49). Homozygous deletion carriers had the longest TTP (70 months). Discussion No clinical impact on chemotherapy response or OS was observed by CTRB2 deletion status. Further studies are needed to identify reliable biomarkers of therapy response in PDAC.